Exploring immune interactions in triple negative breast cancer: IL-1β inhibition and its therapeutic potential - Wilson, Brooke E.; Shen, Qiang; Cescon, David W.; Reedijk, Michael (Frontiers in Genetics, 2023)
Triple negative breast cancer (TNBC) has poor prognosis when compared to other breast cancer subtypes. Despite pre-clinical data supporting an immune targeted approach for TNBCs, immunotherapy has failed to demonstrate the impressive responses seen in other solid tumor malignancies. Additional strategies to modify the tumor immune microenvironment and potentiate response to immunotherapy are needed. In this review, we summarise phase III data supporting the use of immunotherapy for TNBC. We discuss the role of IL-1 in tumorigenesis and summarize pre-clinical data supporting IL-1 inhibition as a potential therapeutic strategy in TNBC. Finally, we present current trials evaluating IL-1 in breast cancer and other solid tumor malignancies and discuss future studies that may provide a strong scientific rationale for the combination of IL-1 and immunotherapy in the neoadjuvant and metastatic setting for people with TNBC.